2016
DOI: 10.1016/j.jadohealth.2015.11.002
|View full text |Cite
|
Sign up to set email alerts
|

Barriers and Facilitators to Health Center Implementation of Evidence-Based Clinical Practices in Adolescent Reproductive Health Services

Abstract: Health center efforts to implement new practice guidelines should include efforts to build the capacity of health center leadership to mobilize staff and resources to ensure that new practices are implemented consistently and with quality.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 21 publications
0
9
0
1
Order By: Relevance
“…A purposive sample of 30 health centers was selected to describe their experiences in implementing evidence-based clinical practices in adolescent reproductive health care at their respective health centers [38]. Centers were selected based on agency type and practice setting to ensure a diverse sample.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…A purposive sample of 30 health centers was selected to describe their experiences in implementing evidence-based clinical practices in adolescent reproductive health care at their respective health centers [38]. Centers were selected based on agency type and practice setting to ensure a diverse sample.…”
Section: Methodsmentioning
confidence: 99%
“…Qualitative data were analyzed using ATLAS.ti software (ATLAS.ti Scientific Software Development GmbH, Berlin, Germany). Data were coded to identify emergent themes in accordance with the principles of grounded theory analysis [38]. As described by Corbin and Strauss [39], grounded theory is an inductive approach to data analysis that “allows the theory to emerge from the data.” In accordance with this approach, interview transcripts and observation notes were first examined line-by-line and assigned “open codes” in the initial phase of data analysis.…”
Section: Methodsmentioning
confidence: 99%
“…Barriers to contraceptive implant uptake and sustained use most frequently included some that do not apply to an HIV prevention implant (eg, irregular or unpredictable menstrual bleeding [ 19 - 21 ]) and others that do apply, such as potential nonmenstrual side effects (eg, headache) [ 20 , 21 ]; perceived or actual high cost of implants [ 22 - 29 ]; patient or provider misconceptions or lack of information about implants (eg, believing that implants are contraindicated for specific patient populations) [ 21 , 23 , 26 - 32 ]; and challenges with access to implants [ 25 , 27 ]. Few studies discuss facilitators of the use of contraceptive implants as a birth control method and instead mostly focus on facilitators of implementation of programs designed to encourage implant use [ 26 , 33 ]. However, the scant body of existing evidence on implant facilitators shows that these include low implant cost, same-day insertion [ 27 ], and the inherent privacy of implants (eg, you can use this contraceptive method with low risk of others finding out) [ 29 ].…”
Section: Resultsmentioning
confidence: 99%
“…At the same A time, barriers such as lack of managerial and financial support, training, and inadequate support have been identified as limiting the implementation and continuity of the YFHSs [23][24][25]. Specifically, Hallum-Montes et al revealed how different factors at the health systems level, such as health center leadership, communication between leadership and staff, staff attitudes and beliefs, use of data for continuous quality improvement, and billing and coding for reproductive health care, work together to influence implementation of new practices in adolescent reproductive health [26].…”
Section: Contextmentioning
confidence: 99%